2019
DOI: 10.47176/mjiri.33.53
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: Language profile in mild cognitive impairment: A prospective study

Abstract: Background:The present study will be a longitudinal investigation of language abilities in individuals with mild cognitive impairment (MCI). The research question will include whether there will be an evidence for language impairment in individuals with MCI, and if so, what aspects of language will be the most affected and whether language abilities will be significantly changed over a 12-month period.Methods: We will diagnose 30 individuals with mild cognitive impairment (MCI), Alzheimer's disease (AD), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Something important to note here is that the COSMA language games refer only to picture naming and do not test or measure verbal, speaking and communication abilities. This is in alignment with literature showing that language impairment in individuals with MCI is primarily present at the semantic level of processing, which is the meaning of words, and at the syntactic processing, which is the structure of phrases and the association of words to each other within phrases and remains partially unaffected [63].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Something important to note here is that the COSMA language games refer only to picture naming and do not test or measure verbal, speaking and communication abilities. This is in alignment with literature showing that language impairment in individuals with MCI is primarily present at the semantic level of processing, which is the meaning of words, and at the syntactic processing, which is the structure of phrases and the association of words to each other within phrases and remains partially unaffected [63].…”
Section: Discussionsupporting
confidence: 90%
“…The study has established the efficacy of COSMA in MCI patients by showing improvement in motor skills and sustained attention within 4 weeks' time of using the application. There are numerous applications in the market focusing on general cognition claiming cognitive improvements, which have no evidence of practical and social benefits to the patients [63]. This is how COSMA differs from the crowded market of cognitive applications, because it has been designed both practically and scientifically for people with cognitive impairments addressing their symptoms and trying to achieve the practical benefits of cognitive improvements in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the median course of disease in the AD-D group (36.00 months) was longer than that in the AD-MCI group (24.00 months), with p -value was close to 0.05, demonstrating that AD was a continuous process, and MCI was the early stage of the disease (Bondi et al, 2017 ). It was previously found that language dysfunction happened at the primary stage of AD and developed over time (Khatoonabadi and Masumi, 2019 ). As the disease progressed from MCI to dementia, a continuous decline in language was observed in patients with AD (Szatloczki et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%